Clinical outcomes of external beam radiotherapy in patients with localized prostate cancer: Does dose escalation matter?. Issue 6 (22nd July 2019) - Lee, Chia Ching; Lim, Keith HC; Chia, David WT; Chong, Yew Lam; Png, Keng Siang; Chong, Kian Tai; Soon, Yu Yang; Tey, Jeremy CS
Abstract: Background: To report outcomes of localized prostate cancer treated with radical external beam radiation therapy (EBRT) in our institution over a 14‐year period, and to determine the impact of dose escalation of prostate cancer outcomes. Methods: Patients with T1–T4 N0 M0 prostate cancer who received radical EBRT between January 2002 and December 2015 were reviewed retrospectively. Clinical data were obtained via the institutional electronic medical records. The primary endpoint was 5‐year overall survival (OS). The secondary endpoints were 5‐year freedom from biochemical failure (FFBF) and treatment toxicities. Results: A total of 200 eligible patients were identified. Median follow‐up duration was 48 months. 13%, 36% and 51% of patients had low‐, intermediate‐ and high‐risk disease. Median dose was 79.2 Gy. The 5‐year OS were 90%, 87% and 78% and FFBF were 94%, 100% and 81% for low‐, intermediate‐ and high‐risk patients, respectively. Multivariable analysis showed that Eastern Cooperate Oncology Group performance status 2 and Gleason grade group 5 were independent predictors of worse OS. The incidence of grade ≥2 proctitis was 24.5%. Dose escalation was significantly associated with increased incidence of grade ≥2 proctitis (odd ratio, 4.42; 95% confidence interval, 1.95–10.08; P  < 0.01). Conclusion: Men with localized prostate cancer treated with EBRT in our population had excellent 5‐year OS and biochemical outcomes. Dose escalation did not significantly improve these outcomes but was associated with significantly increased risk of grade ≥2 proctitis in our population. Future studies should be performed to identify patients who will benefit the most from dose‐escalated EBRT.